Analytical Hierarchy Process Method to Determine Student Satisfaction Level with Academic Services - Gilang Armawan Saka; Abdul Halim Hasugian (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Student satisfaction is an important aspect in the world of higher education that must be taken seriously. This is because students are the main stakeholders in the learning process and the development of educational institutions. The purpose of this research is to identify factors that affect student satisfaction with academic services and to apply the AHP method in determining the relative weight of each assessment factor that affects student satisfaction with academic services. The results showed that the AHP method helped weight alternatives and criteria with a weight scale of 1 - 9 according to the Saaty table, after weighting the alternatives, then ranking using the AHP method to get the final score, ranking 1 was obtained by Conducive Lecture Room with a final score of 0.084 and ranking 21 was obtained by Regulation with a final score of 0.037, therefore the level of student satisfaction with Conducive Lecture Room was the highest. The design of the application is carried out by conducting research in the academic science of UINSU by collecting student assessment data on academic services, after the data is collected, the weighting of each academic service is carried out and then entered into the application that has been built using the AHP method, influencing factors based on the weight of criteria and sub-criteria.